A Systematic Review on Enhancing Knowledge Management Capability Model for Lecturers Based on Digital Technology - Indrati, Iman; Suharyati, Henny; Wulandari, Dian (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Rapid technological advances demand innovation in teaching while simultaneously creating challenges in adapting and utilizing digital tools. This study, using the PRISMA-based Systematic Literature Review (SLR) method, explores a model for strengthening Knowledge Management (KM) through digital literacy. The study's findings highlight that strengthening KM with digital technology is key to creating an efficient and innovative academic ecosystem. Utilizing online learning platforms and digital collaboration tools makes knowledge sharing more effective. Furthermore, ongoing training and adequate infrastructure support encourage a more collaborative learning environment. Universities need to design and implement a Knowledge Management integration model that aligns with technological advancements and academic needs. A holistic approach, encompassing technology, processes, and organizational culture, enhances digital literacy and the culture of knowledge sharing among lecturers, ultimately enhancing the effectiveness of knowledge management and academic competitiveness in the digital era.